Domestic violence related disclosure among women and girls in Ethiopia: a systematic review and meta-analysis - Berhanu Boru Bifftu; Berihun Assefa Dachew; Bewket Tadesse Tiruneh; Lemma Derseh Gezie; Yonas Deressa Guracho (BMC, 2019)
Abstract Background Domestic violence is common public health problem. Domestic violence related disclosure is an important first step in the process of prevention, control and treatments of domestic violence related adverse effect. Thus, this systematic review and meta-analysis aimed to determine the pooled prevalence of domestic violence related disclosure and synthesize its associated factors. Methods We followed the PRISMA Guidelines to report the results of the finding. Databases including PubMed, Cochrane Library and Web of Sciences were searched. The heterogeneity between studies was measured by the index of heterogeneity (I2 statistics) test. Funnel plots and Egger's test were used to determine publication bias. Moreover, sensitivity analysis was carried out. To calculate the pooled prevalence, a random effects model was utilized. Results Twenty one eligible studies were included in this systematic review and meta-analysis. The pooled prevalence of domestic violence related non-disclosure was found to be 36.2% (95% CI, 31.8-40.5%). Considering violence as normal or not serious, shame, embarrassment and fear of disclosure related consequences were the common barriers for non-disclosure. Conclusion More than one third of women and girls were not disclosed their experience of domestic violence. The finding of this study suggests the need of evaluation and strengthening of the collaborative work among different sectors such as: policy-makers, service providers, administrative personnel and community leaders including the engagement of men partner. This study also suggests the needs of women empowerments against the traditional belief, attitude, and practice.